2017
DOI: 10.5435/jaaosglobal-d-17-00034
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Silver Nylon Dressing Following Total Hip and Knee Arthroplasty Decreases the Postoperative Infection Rate

Abstract: Introduction:Prosthetic joint infection (PJI) is a potentially catastrophic complication of total joint replacement. Our purpose was to determine whether the use of a silver dressing reduces the incidence of superficial and deep PJI following primary total hip replacement and total knee replacement.Methods:A case-control study of primary total hip replacement and total knee replacement was performed to compare the incidence of superficial and deep PJI in patients who received a silver nylon dressing with patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…In 2019, Stanirowski et al 15 published the results of a randomised controlled on women (N = 543) who underwent caesarean section, which revealed that the use of bacterial-binding dressings following caesarean section could reduce the incidence of SSI and healthcare costs. In 2017, Tisosky et al 9 reported a positive impact of application of antimicrobial dressing on the postoperative wound on the reduction of SSI incidence. Their case-control study (N = 834) discovered that the use of a silver dressing significantly reduced the incidence of superficial and deep prosthetic joint Table 2a.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, Stanirowski et al 15 published the results of a randomised controlled on women (N = 543) who underwent caesarean section, which revealed that the use of bacterial-binding dressings following caesarean section could reduce the incidence of SSI and healthcare costs. In 2017, Tisosky et al 9 reported a positive impact of application of antimicrobial dressing on the postoperative wound on the reduction of SSI incidence. Their case-control study (N = 834) discovered that the use of a silver dressing significantly reduced the incidence of superficial and deep prosthetic joint Table 2a.…”
Section: Resultsmentioning
confidence: 99%
“…8 Silver dressings provide extensive protection against bacteria, fungi and viruses, including nosocomial pathogens, methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant Enterococci (VRE), making them a valuable adjunct in the prevention and treatment of infection. In 2017, Tisosky et al 9 conducted a clinical trial showing that the use of silver dressings significantly reduced the incidence of superficial and deep prosthetic joint infection following total joint replacement. A literature review 10 published in 2014 reported that silver nylon dressings are associated with a reduced risk of SSI in small studies across several specialities, including colorectal surgery, neurosurgery, spinal surgery and some cardiac and orthopaedic procedures, although the authors recommend larger powered trials on these cohorts to determine the comparative effectiveness of silver nylon dressings in the prevention of SSIs.…”
Section: A Silver-based Antimicrobial Dressing For the Prevention Of mentioning
confidence: 99%
“…However, by themselves, large silver nanoparticles can also pin and inhibit the growth of microbes without taking the Ag + ions role into consideration 63 . Lastly, silver nanoparticles or ions can be incorporated into or deposited onto the nylon by mixing them with the melted polymer or via soaking nylon fibers in an aqueous solution containing the nanoparticles/ions 64–66 …”
Section: Antimicrobial Strategiesmentioning
confidence: 99%
“…ICM delegates concluded that occlusive and silver-impregnated dressings reduce the rate of wound complications, SSI, and PJI compared to standard gauze dressings and should be considered for routine use in arthroplasty [129]. One caveat is that formal costeffectiveness studies are needed to see whether the increased cost of the occlusive, silver-impregnated compared to standard dressings justify routine use vs selective use, after accounting for the reduction in cost with decreased postoperative infection [114,130].…”
Section: Wound Dressingmentioning
confidence: 99%